STRATEGY HUMAN RESOURCE DEVELOPMENT (SOURCE POWER HUMAN) TO IMPROVE FARMERS' WELFARE PALM OIL IN GUNUNG MERIAH DISTRICT, DELI SERDANG REGENCY - Giska Patrisia Sembiring; Purjianto (RADJA PUBLIKA, 2026)
This study aims to analyze the quality of human resources (HR) among oil palm farmers, identify factors that hinder HR development, formulate effective HR development strategies, and analyze their impact on improving farmer welfare in Gunung Meriah District, Deli Serdang Regency. The study used a descriptive method with a qualitative approach. The research location was determined purposively in Gunung Meriah District with 69 farmers selected using simple random sampling technique from a population of 221 farmers. Data were collected through semi-structured interviews, field observations, documentation, and literature studies. Data analysis was conducted using a SWOT analysis using the IFAS, EFAS, and SWOT matrices. The results showed that the quality of farmers' HR is still relatively low, characterized by minimal access to training and extension, low technical cultivation skills, and dependence on informal information sources. The main obstacles to HR development come from limited capital and technical knowledge, as well as external factors such as the unavailability of extension programs, poor road infrastructure, and weak farmer institutions. The SWOT analysis places farmer human resource development in Quadrant I (aggressive strategy), indicating significant strengths and opportunities to be exploited. Recommended priority strategies include increasing Good Agricultural Practices (GAP)-based extension services, strengthening farmer groups and cooperatives, expanding access to capital, utilizing information technology, and improving supporting infrastructure. Planned and sustainable human resource development is a key factor in increasing the productivity, competitiveness, and welfare of oil palm farmers in Gunung Meriah District